What Do We Know About Teacher Leadership? Findings From Two Decades of Scholarship - York-Barr, Jennifer; Duke, Karen (Review of Educational Research, 2004)
The concept and practice of teacher leadership have gained momentum in the past two decades. Teachers are assuming more leadership functions at both instructional and organizational levels of practice. Empirical literature reveals numerous small-scale, qualitative studies that describe dimensions of teacher leadership practice, teacher leader characteristics, and conditions that promote and challenge teacher leadership. Less is known about how teacher leadership develops and about its effects. In addition, the construct of teacher leadership is not well defined, conceptually or operationally. Future research focused on the differentiated paths by which teachers influence organizational capacity, professionalism, instructional improvement, and student learning has the potential to advance the practice of teacher leadership. A conceptual framework is offered to guide such inquiry.